Location of death among patients presenting with cardiovascular disease to the emergency department in the United states. Issue 4 (6th February 2021) - Kwok, Chun Shing; Wong, Chun Wai; Ravindran, Roshini; Michos, Erin D.; Khan, Safi U.; Abudayyeh, Islam; Mohamed, Mohamed; Parwani, Purvi; Thamman, Ritu; Elgendy, Islam Y.; Van Spall, Harriette G. C.; Mamas, Mamas A.
Abstract: Background: In‐hospital deaths are an important outcome and little is known about deaths in the emergency department (ED). Among patients who died of cardiovascular diseases (CVD), we assessed causes of death, temporal trends and the relative distribution of deaths in the ED versus hospital. Methods: Using the United States Nationwide Emergency Department Sample, we conducted a retrospective study of patients presenting to the ED with a primary diagnosis of CVD between 2006 and 2014. We used descriptive statistics to describe causes of deaths, temporal trends and location of death. Results: During the study period, there were 27 144 508 visits to the ED with CVD diagnoses ( 2% of all ED visits, ). The most common CVD diagnoses were heart failure (n = 8 571 598), acute myocardial infarction (n = 4 827 518) and atrial fibrillation/flutter (n = 4 713 241). There were a total of 2.2 million deaths caused by the CVD, with the majority (57.6%) occurring in the ED. Cardiac arrest was the most common cause of in‐hospital death (n = 1 225 095, 55.3%), followed by acute myocardial infarction (n = 279 310, 12.6%), heart failure (n = 217 367, 9.8%), intracranial hemorrhage (n = 168 009, 7.6%) and ischemic stroke (n = 151 615, 6.8%). The proportion of deaths in the ED for these causes were 91.9% cardiac arrest (n = 1 173 471), 3.6% acute myocardial infarction (n = 46 909), 1.0% heart failure (n = 12 599) and 1.1% intracranial hemorrhage (n = 13 579). There was a decrease in death for most CVDs over time. Conclusions: Inpatient CVD admissions and their associated death may not be a robust measure of the national burden of CVD since ED death—which are common for some conditions—are not captured.